PENGARUH KOMUNIKASI BISNIS DAN STRATEGI ALIANSI TERHADAP KINERJA MANAJEMEN RANTAI PASOK PADA PT. “XXX” BANDUNG - Jamaludin, Maun (Ilmu Komunikasi, FISIP Universitas Pasundan, 2021)
Abstract Very tight competition requires business managers to create new models in managing the flow of products and information. Due to the smooth supply of raw materials PT.